2018
DOI: 10.1638/2017-0062.1
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Serosurvey of Avian Influenza H5 Among Wild Birds in Nakhon Sawan Province, Thailand

Abstract: An outbreak of HPAIV H5N1 in Nakhon Sawan province, Thailand, in 2004 caused sporadic deaths of Asian openbill storks ( Anastomus oscitans). An investigation was undertaken to determine if this virus occurs and circulates in wild birds in Nakhon Sawan province. Following the outbreak, a widespread serosurvey was conducted using the hemagglutination inhibition assay and microneutralization assay to detect antibodies against AIV H5. From 2007 to 2014, blood was collected from a total of 753 wild birds, represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…The outbreak of H5N1 has not been reported in Thailand since 2008. However, sero-surveillance of IAV revealed that antibody against IAV subtype H5 can be detected in free-grazing ducks and wild birds (Beaudoin et al, 2014;Poltep et al, 2018). There are several reports of IAV-H5 reassortants with different NA subtypes, including N1, N2, N3, N5, N6, and N8, and subsequently the viruses can cause outbreaks in poultry and in Asia, e.g.…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…The outbreak of H5N1 has not been reported in Thailand since 2008. However, sero-surveillance of IAV revealed that antibody against IAV subtype H5 can be detected in free-grazing ducks and wild birds (Beaudoin et al, 2014;Poltep et al, 2018). There are several reports of IAV-H5 reassortants with different NA subtypes, including N1, N2, N3, N5, N6, and N8, and subsequently the viruses can cause outbreaks in poultry and in Asia, e.g.…”
Section: List Of Abbreviationsmentioning
confidence: 99%